2021
DOI: 10.1109/jlt.2021.3093201
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Microwave Photonic Spectral Shaping For Linearization and Spurious-Free Dynamic Range Enhancement

Abstract: Integrated microwave photonics (MWP) is a fast growing area where high frequency microwave signals are processed in the optical domain, merging key advantages of both microwave photonics and photonic integrated circuits (PICs) technologies including low-loss, reconfigurability, advanced functionality, enhanced stability, and reduced footprint. Plenty of functionalities have been demonstrated in integrated MWP, especially based on spectral shaping technique, where the phase and amplitude of the optical spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…However, most integrated microwave photonic systems do not meet these metrics, or do not report them. Recent demonstrations of MWP filters with optimised link performance have come close to the target metrics, using a combination of fibre-based and chip-based components [45], [46], [158]. For example, Daulay et al reported an MWP filter using on-chip processing that achieved a link gain of 10 dB, and noise figure of 15 dB, and SFDR of 116 dB.Hz 2/3 [158].…”
Section: B Integrated Platforms and Rf Link Performancementioning
confidence: 94%
See 1 more Smart Citation
“…However, most integrated microwave photonic systems do not meet these metrics, or do not report them. Recent demonstrations of MWP filters with optimised link performance have come close to the target metrics, using a combination of fibre-based and chip-based components [45], [46], [158]. For example, Daulay et al reported an MWP filter using on-chip processing that achieved a link gain of 10 dB, and noise figure of 15 dB, and SFDR of 116 dB.Hz 2/3 [158].…”
Section: B Integrated Platforms and Rf Link Performancementioning
confidence: 94%
“…On-chip MWP processors, for example RF photonic filters, have been demonstrated using integrated optical micro-ring resonators (MRRs) [32], [45], [46]. Although good performance has been achieved, MRR-based processing has limited spectral flexibility, as the shape of the photonic resonance is determined by the intrinsic waveguide losses and fixed structural properties of the MRR.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we implement third-order intermodulation distortion (IMD3) cancellation technique using complex multi-order sidebands spectral shaping as we previously reported [42,58,59] (see Supplmentary Notes D and E for the details of the linearization technique). In this experiment, light is sent to a phase modulator (PM) (Fig.…”
Section: High Gain and Low Noise Figure Mwp Filtermentioning
confidence: 99%
“…Achieving simultaneous on-chip programmability and high RF performance requires integration of new types of photonic devices. A versatile modulation transformer (MT) that can tailor the phases and amplitudes of optical carrier and RF sidebands has recently identified as a key element for enhancement of dynamic range [40][41][42]. On the other hand, a programmable resonator such as a double-injected ring resonator (DI-RR) [43] can provide a large number of filtering functions in a device.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have focused on combining functions with reduction of noise figure through optical carrier processing [7], [8], but linearization methods, which are critical for achieving high spurious free dynamic range (SFDR), are largely absent in integrated MWP devices. We have recently demonstrated that linearization can be done in a photonic chip through advanced MWP spectral shaping [9]. The basic idea is tailoring the phase and amplitude of optical carrier and multi-order sidebands to make the thirdorder intermodulation distortion (IMD3) terms from different beating products destructively interfered [9], [10].…”
Section: Introductionmentioning
confidence: 99%